What EFL Learners Say about YouTube Use to Improve Pronunciation in a Blended Learning Environment - Purnamasari, Asri (JET (Journal of English Teaching), 2018)
YouTube is the most widely accessed video-sharing platform in the world. It offers not only millions of videos of music, movie, sport, talk shows, and news but also educational videos. Today’s students generally like YouTube. Therefore, it offers great opportunities for students and teachers to enhance EFL learning and teaching, including pronunciation improvement. This article is part of a larger study on EFL learners’ perception of using YouTube to improve English pronunciation in a blended learning environment. It employed the explanatory sequential mixed methods design and involved 26 freshmen majoring in Management at a private university in Jakarta, Indonesia. Data was collected using a questionnaire and interview. The results showed that: (1) the participants were so familiar with YouTube and encountered no difficulty to access and use it; (2) a majority of the participants found YouTube interesting and fun; (3) the participants viewed learning with YouTube advantageous because it presents the instructional materials in letters, sounds, and pictures at once; and (4) most participants found YouTube interesting and motivating, and thus it improved their pronunciation skills.